Method for raising pigs - HUANG ZUDONG (2017)
The invention belongs to the technical field of livestock breeding and in particular relates to a method for raising pigs. The method comprises the following steps: (1) establishing a pig farm; (2) selecting boars; (3) performing feeding management: feeding the pigs in a free feeding mode, expelling the pigs from a hog house to a sports field to move for 1-3 times every day, 1-3h per time; and (4) performing pig farm management: when the pigs move in the sports field, cleaning the hog house, wherein the sports field is cleaned once every 1-3 days, and spraying a disinfectant to the hog house and the sports field once every 3-7 days to disinfect. The method can promote digestive absorption of the boars and enhance the immunity of the pigs. A clean survival environment can be provided for the pigs, the morbidity rate of the pigs is decreased, healthy growth of the pigs is accelerated, and the pork is good in flavor. 本发明属于畜禽养殖技术领域，具体涉及种养猪的方法。所述方法包括以下步骤：(1)建立猪场；(2)选种；(3)饲养管理：采取自由取食方式饲喂，每天将猪从猪舍内赶到运动区运动1-3次，每次1-3h；